ANALYSIS OF THE EFFECT OF FINANCIAL RATIOS ON STOCK UNDERPRICING IN INITIAL PUBLIC OFFERINGS ON THE INDONESIA STOCK EXCHANGE - Andre Kussuma Adiputra; Poly Endrayanto Eko Christmawan; Angellin Corry Astavia Tlonaen (Jurnal Ekonomi, 2023)
This study aims to identify financial ratios that affect underpricing on the IDX in the 2010-2022 period. This type of research can be categorized as quantitative research. The population of this study includes all companies that go public or conduct initial public offerings (IPOs) on the IDX in a certain period from 2010 to 2020. This research sample was taken using purposive sampling technique. This research was carried out by conducting multiple regression. Based on the results of the discussion and explanation that has been presented in the four chapters above, it can be concluded that Return on Asset (ROA), Debt to Equity Ratio (DER), Profit Margin (PM), Payout Ratio (PR), Earning per Share (EPS), and Current Ratio (CR) simultaneously have a significant effect on Stock Underpricing. Based on the results of the T test (Partial) shows that Return on Asset (ROA), Earning per Share (EPS), and Current Ratio (CR) partially have a significant negative effect on stock underpricing. While the partial test results on Debt to Equity Ratio (DER), Profit Margin (PM), and Payout Ratio (PR) show that these three variables have no significant effect on stock underpricing.